Carcinosarcoma of the Uterus: Report of a Case with Invasion of the Urinary Bladder, Resembling Mullerianosis with Malignant Transformation - Ogata, Daniel Cury (2012)
Introduction: Uterine carcinosarcoma are infrequent neoplasms, corresponding to 3-9% of all gynecologic neoplasms only. They represent 48% of all sarcomas, with an incidence of 8.2 per 1 million women/year. The main clinical manifestations are postmenopausal vaginal bleeding and abdominal pain. Tumors are morphologically characterized by epithelial and stromal elements. They can eventually invade adjacent structures, including the urinary bladder. Case Report: We present a case of uterine carcinosarcoma with invasion of the urinary bladder resembling mullerianosis with malignant transformation. A 69 year-old female patient had macroscopic hematuria as the single complaint. During diagnostic investigations, after cystoscopy with anatomical and pathological exam was performed, the hypothesis of mullerianosis with benign transformation was suggested. The patient was thus submitted to surgical resection of this lesion. During the surgical procedure, we noticed the existence of a uterine tumor mass that was invading the urinary bladder, and after anatomical and pathological analysis, it was identified as a carcinosarcoma of the uterus with invasion of the urinary bladder. Conclusion: Unusual manifestation of diseases with great malignant potential, in addition to delay the process of diagnosis, directly interferes with the patient’s prognosis.